ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN BUKU DENGAN KONSINYASI BERBASIS CLIENT/SERVER - Pujianto, Pujianto (Jurnal Informatika, 2012)
On a trade business there are three methods of purchasing and selling; cash purchasing or selling method, credit and trade cooperation. The book sale system commonly still uses cash purchasing or selling system and credit. Automatically, this thing will become the business obstacle for the suppliers whenever they want to put their books on the book shops for sale. The trade method of putting books and selling is called as trade cooperation. It become one of the trendy purchasing or selling methods. This thing also needs a solution to prevent the appearance of repetitive misunderstanding.The method used in this research is modified waterfall method. The method was developed by Winston Royce. On this method, the research did library study, analyzing the system demand, designing the system and face to face method, creating system and testing it.The result of the research is an information system of book sale based on client or server. This sale information system also uses cash sale model, credit and cooperation. The sale using this trade cooperation is implemented to ease the bookshop owner in monitoring the books sold in the cooperation system.Keyword : Information System, Client/server and trade cooperation